Practical activities for Physical Education class aimed at students with special educational needs. - Acha Domeño, Aitor (Pulso. Revista de educación, 2004)
This article discusses the teaching approach for Physical Education practices for students with special educational needs in the second year of the Special Education programme at the University School Cardenal Cisneros. We will introduce the academic characteristics of the subject and discuss the number of credits allocated to this subject within the overall teaching programme. After, we will examine the objectives of the subject and the techniques and resources employed to facilitate its instruction. Finally, we will present our findings on the implementation of the practical sessions and present statistical data on their outcomes over the past three academic years.